Cryopreservation of mouse embryo using vitrification method (Journal of Laboratory Animal Science, 2021)
Cryopreservation plays an important role in storing the embryos of unwanted strains of laboratory animals in liquid  nitrogen and maintaining the lines in smallest available space. This not only helps in curtailing the unwanted  expenditure of maintaining these lines but also saving time and energy. Laboratory Animal Facility of ACTREC is  maintaining various strains of mice, rats and hamsters. Our facility has established rodent embryo cryo-bank which  acts as a backup for the valuable strains. Initially, we have made a successful attempt by slow freezing and fast thawing  method. Considering the recent advances in cryopreservation technique and success rate, we report here an attempt  of the cryopreservation of mouse embryos by vitrification technique. In the present study, in all 851 embryos were  collected from 132 donor female mice from four strains of different background. An average gain of 7 embryos per  female was recorded by natural mating. Collected embryos were stored in 45 cryovials. As a quality control measure  and to check the efficiency of newly adopted vitrification protocol, we thawed few vials at periodic interval. The  percentage of recovery of embryos was ranging from 91.67% to 97.5%. The lower percentage of 91.67% was found  in Smo/Smo strain, while higher percentage of 97.5% was found in outbred, Crl: CD1 (ICR) strain. These embryos were  kept in CO2 incubator for 1 hr for maintaining morphology. After incubation, the percentage of embryos maintained  morphology in these four strains was ranging from 57.33% to 100%. The lowest percentage 57.33% of morphology  was found in spontaneous mutant S/RV/Cri-ba strain. The morphology maintained embryos were surgically transferred  in 1.5 day post-coitus pseudo-pregnant female mice of CD1 strain. Out of 17 females, 12 females became pregnant  and delivered total 51 live pups which were subsequently weaned and allowed to breed further. The percentage of  embryo transferred Vs live births was ranging from 14.89% to 31.03%. Based upon the results, it is evident that there is  an increase in overall success of the newly adopted technique of vitrification which is simple and less time consuming  than slow freezing and fast thawing method.
Keywords: Cryopreservation; Embryo; Ethylene glycol; Vitrification; Asynchronous transfer